Hirata's disease - Otoya, Enrique (2019)
It is showed the case of a 39 year-old woman with Graves disease and episodes of persistent symptomatic hypoglycemia, with high levels of C-peptide and insulin. The study of images did not show the presence of tumors. Anti-insulin antibodies were positive and the genetic study with the HLA typing class II expressed the alleles of DRB1*04 and DQB1*03* 02 related to disease of Hirata. This would be the first case reported in our country.